Supreme Court Justices' Economic Behaviour: A Multilevel Model Analysis. (22nd December 2015) - Skiple, Jon Kåre; Grendstad, Gunnar; Shaffer, William R.; Waltenburg, Eric N.
Abstract : Supreme Court justices are overlooked, but important, national policy‐making players who render final and consequential decisions in cases on economic conflicts. The research question asks what forces explain the decisional behaviour of Supreme Court justices in economic rights cases between a private and a public party. Theoretically, the decisional behaviour of an individual justice is a function of his or her notion as to what makes 'good' law, pursued in a cultural‐collegial setting that is oriented by majoritarian requirements, while constrained by the legal nature of the case being considered. Empirically, all economic decisions made by Norwegian Supreme Court justices in five‐justice panels from 1963 to 2012 are analyzed. Our multilevel model demonstrates that individual, collegial and case‐level forces all contribute to explain the justices' votes. These results suggest that case‐related dynamics, such as who the plaintiff is or the amount of disagreement between justices, matter, but also that ideology – via appointment mechanisms – matters when a nation's high court justices decide economic cases. Understanding the foundational assumptions and the institutional procedures is vital when transporting judicial behaviour models across polities.